2020
DOI: 10.1111/bjdp.12326
|View full text |Cite
|
Sign up to set email alerts
|

Gender Intensification and Gender Generalization Biases in Pre‐adolescents, Adolescents, and Emerging Adults

Abstract: The gender intensification hypothesis claims that the socialization pressures of early adolescence lead to the adoption of traditional sex‐typed roles. We tested this proposal by examining how extensively children (Mage = 9.39 years; N = 69, 31 female), early adolescents (Mage = 12.06 years; N = 70, 36 female), middle adolescents (Mage = 14.81 years; N = 65, 37 female), and emerging adults (Mage = 18.51 years; N = 70, 37 female) made generalizations from vignettes about male and female characters who had stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
2
22
1
Order By: Relevance
“…A great deal of research conducted in Western nations indicates that women and men are socialized to act in accordance with stereotypical gender roles: Females are encouraged to be nurturing and socially connected, whereas males are encouraged to be independent and autonomous (Helgeson, 1994;Klaczynski et al, 2020;Martinez et al, 2019). In a recent systematic review of gendered parenting in US, Canada, Australia and Western Europe, it has been shown that parents respond differently to daughters and sons (Morawska, 2020).…”
Section: Agency and Communionmentioning
confidence: 99%
See 3 more Smart Citations
“…A great deal of research conducted in Western nations indicates that women and men are socialized to act in accordance with stereotypical gender roles: Females are encouraged to be nurturing and socially connected, whereas males are encouraged to be independent and autonomous (Helgeson, 1994;Klaczynski et al, 2020;Martinez et al, 2019). In a recent systematic review of gendered parenting in US, Canada, Australia and Western Europe, it has been shown that parents respond differently to daughters and sons (Morawska, 2020).…”
Section: Agency and Communionmentioning
confidence: 99%
“…Similarly, parents in Western societies prefer gender-typed toys for their children, with stereotypically feminine toys related to nurturance and care and stereotypically masculine toys related to aggression and action (Blakemore & Centers, 2005;Kollmayer et al, 2018a). Thus, the gendered self-concepts and selfdescriptions of women and men may reflect characteristics that have been built through socialization mirroring societal expectations for men and women (Athenstaedt, 2003;Eagly et al, 2000;Klaczynski et al, 2020;Martinez et al, 2019).…”
Section: Agency and Communionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the analysis of the results, the sample of minors was divided into three age groups: G1, 6-8 years (n = 3098), G2, 9-11 years (n = 3749), and G3, 12-14 years (n = 4597). This division responds to the need to divide the sample equitably and that the older children (those who in previous research are usually included as "pre-adolescents") were all in the same group [33,34].…”
Section: Discussionmentioning
confidence: 99%